Is weight a predictive risk factor of postoperative tonsillectomy bleed?. Issue 3 (14th May 2018) - Ordemann, Allison G.; Hartzog, Anna Jade; Seals, Samantha R.; Spankovich, Christopher; Stringer, Scott P.
Abstract : Objective: To determine if a correlation exists between weight‐for‐age percentile and post‐tonsillectomy hemorrhage in the pediatric population. Study Design: Retrospective study. Methods: 1418 patients under the age of 15 who underwent tonsillectomy with or without adenoidectomy at a tertiary children's hospital between June 2012 and March 2015 were included in this retrospective study. Patient demographic information, operative and postoperative variables, as well as category and day of postoperative tonsillectomy bleed, if one occurred, were recorded. Fisher's exact and ordinal logistic regression analyses were performed on the full cohort. Results: The overall post‐tonsillectomy hemorrhage prevalence was found to be 2.2%, with primary and secondary rates of 0.78% and 1.34%, respectively. Weight‐for‐age percentile, sex, indication for or method of tonsillectomy, or postoperative use of NSAIDs, antibiotics or narcotics were not significantly associated with post‐tonsillectomy hemorrhage. There was a significant relationship between postoperative use of dexamethasone and higher rate of Category 3 post‐tonsillectomy hemorrhage ( P  = .028). Conclusion: The post‐tonsillectomy hemorrhage rate in our study is consistent with that cited in the literature. No correlation was demonstrated between weight‐for‐age percentile and occurrence of post‐tonsillectomy hemorrhage. Postoperative administration of dexamethasone was associated with a significant increased rate of post‐tonsillectomy hemorrhage requiring surgical intervention, a novel finding. Level of Evidence: 4